Fix-it and forget-it lightly : 600 healthy, low-fat recipes for your slow cooker - Good, Phyllis Pellman, 1948- (Intercourse, PA : Good Books, 2011)
This favorite guide to quick and easy-to-prepare slow-cooker food has sold more than 1.2 million copies. It is now available in this Revised and Updated edition! It is possible to have it all: food from your slow cooker that is scrumptious and low-fat, and convenient to make. Here are 600 recipes that are mouth-watering but guilt-free. Now you can choose healthy, light dishes, fix them quickly, and then forget about them until mealtime.
The main courses -- Soups, stews, and chilis -- Vegetables -- Desserts -- The extras.
Includes index.
Keywords: Electric cooking, Slow; Quick and easy cooking; Low-fat diet -- Recipes; Cookbooks